Shaping national identity through loss: Alianza Lima and its elimination from Copa Libertadores 2010 - Pahuacho, Alonso (2020)
The aim of this article is to investigate the role played by the printed press in the construction of Peruvian national identity within the context of sporting loss in an international competition. Media representation of Peruvian sporting nationalism can be used as a lens through which to examine how elements of the national identity were represented, reproduced and reinforced by the media following the Alianza Lima soccer team’s performance. Through the Critical Discourse Analysis (CDA), this research reveals that after the elimination of the Peruvian team, the printed press constructed the failure since a double perspective: attribute the defeat due to external factors (blaming the referee) and dignify it as an epic deed.